1997
DOI: 10.1007/bf02348216
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Process of the Symptom Development and Resistance Mechanism in Pine Wilt Disease

Abstract: Pathophysiological changes during the symptom development of pine wilt disease are reconsidered from recent investigations. The symptom development is divided into two stages: the early and the advanced stages. In the early stage, small number of nematodes migrate in cortex, then in xylem of the stem, and induce denaturation and necrosis of parenchyma cells. These changes in parenchyma are regarded as defense reactions of pines which result in terpene synthesis in xylem cells and embolism in tracheids. Such ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
112
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 35 publications
5
112
2
2
Order By: Relevance
“…It has been previously demonstrated that ethylene production increases in pine trees during PWN invasion, suggesting that increased ethylene levels are, at least partially, responsible for the development of PWD symptoms (Mori and Inoue 1986;Fukuda et al 1994;Fukuda 1997). The data presented here are consistent with the possibility that, through ACC deaminase production, P. putida UW4 reduces the deleterious ethylene levels in pine seedlings induced by PWN invasion, thereby decreasing the disease severity and progression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been previously demonstrated that ethylene production increases in pine trees during PWN invasion, suggesting that increased ethylene levels are, at least partially, responsible for the development of PWD symptoms (Mori and Inoue 1986;Fukuda et al 1994;Fukuda 1997). The data presented here are consistent with the possibility that, through ACC deaminase production, P. putida UW4 reduces the deleterious ethylene levels in pine seedlings induced by PWN invasion, thereby decreasing the disease severity and progression.…”
Section: Discussionsupporting
confidence: 89%
“…If the pathogen action is intense, the autocatalytic ethylene synthesis and the consequent high levels of ethylene can be responsible for plant damage and ultimately its death (van Loon 1984). Interestingly, several authors reported an increase of ethylene levels in pine upon PWN invasion, and suggest that ethylene can play a role in PWD development (Mori and Inoue 1986;Fukuda et al 1994;Fukuda 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the susceptibility of the transition zone to cavitation. Previous studies suggest that the death of phloem and cambium is also an important symptom that occurs at the same time as embolisms in the current-year xylem (Fukuda et al, 1992b;Fukuda, 1997). In our observations, the phloem and cambium did not dry up (die) until runaway embolism occurred (Figs.…”
Section: Discussionsupporting
confidence: 63%
“…Because the nematode itself rarely enters into the tracheids of living pine (Ichihara et al, 2000), some researchers have attributed the abrupt increase in embolized tracheids to modification of the surface tension of xylem sap (Ikeda and Kiyohara, 1995), cellulase production of PWN (Odani et al, 1985), released oily substance occluding the tracheid lumen and pit membrane (Nobuchi et al, 1984;Hara and Futai, 2001), and abnormal leaks of oleoresin from resin canals (Sasaki et al, 1984). In addition, some researchers have suggested that some compounds, such as terpenoids released from parenchyma cells (Kuroda, 1989(Kuroda, , 1991 and ethylene produced in xylem (Fukuda, 1997), can induce xylem embolism, based on the results of artificial injection of these compounds into the stem. In coniferous species, a significant increase of the cavitation event by water stress is usually synchronized with a drastic decrease of water potential (Brodribb and Cochard, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation